The impact of Internet use on workers' job satisfaction: Heterogeneous and mediating analyses. - Xiong, Bin; Yu, Baocheng; Chen, Yuntao (Work, 2026)
Background: The positive emotions brought about by high levels of job satisfaction are beneficial to the physical and mental health of workers. The Internet offers a variety of resources and is a valuable new tool for increasing job satisfaction. Objective: Analyzing data of 29,315 respondents aged 16 years and older, this study aims to explore how Internet use affects workers' job satisfaction and heterogeneity in the digital age. Methods: Using panel data during 2016–2020, we employ the Ologit model, Oprobit model, and other methods to examine the impact of Internet use on workers' job satisfaction, heterogeneity and the four channels through which this impact is transmitted. Results: First, Internet use can increase workers' job satisfaction, and has significant positive effects on job income satisfaction, safety satisfaction, time satisfaction and environmental satisfaction. Second, the impact of Internet use on job satisfaction is mainly achieved through its impact on unblocking information channels, enhancing job ability, improving work efficiency and increasing income. Third, the effectiveness of Internet varies across industries and age groups. Internet use is positively correlated with job satisfaction of workers in secondary and tertiary industries, but negatively correlated with job satisfaction of workers in primary industries. Meanwhile, this positive impact is significant among young people aged 16–44, but when workers enter middle and old age, the Internet use has no significant impact on job satisfaction. Conclusions: The results suggest that Internet use can increase workers' job satisfaction, and its effectiveness varies by age and industry. To improve workers' work enthusiasm and mental health, enterprises should take measures to encourage the use of the Internet.